2018
DOI: 10.3847/1538-4357/aaed25
|View full text |Cite
|
Sign up to set email alerts
|

A Theory for the Variation of Dust Attenuation Laws in Galaxies

Abstract: In this paper, we provide a physical model for the origin of variations in the shapes and bump strengths of dust attenuation laws in galaxies by combining a large suite of cosmological "zoom-in" galaxy formation simulations with 3D Monte Carlo dust radiative transfer calculations. We model galaxies over 3 orders of magnitude in stellar mass, ranging from Milky Way like systems through massive galaxies at high-redshift. Critically, for these calculations we employ a constant underlying dust extinction law in al… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
195
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(220 citation statements)
references
References 151 publications
25
195
0
Order By: Relevance
“…This result is well known and is attributed to the star-dust geometry (Witt & Gordon 1996;Narayanan et al 2018). Narayanan et al (2018) have shown that steeper slopes may arise either by a large fraction of obscured young stars or by a significant fraction of unobscured old stars. Consequently, galaxies with older stellar populations exhibit steeper attenuation curves.…”
Section: Attenuation Lawmentioning
confidence: 59%
“…This result is well known and is attributed to the star-dust geometry (Witt & Gordon 1996;Narayanan et al 2018). Narayanan et al (2018) have shown that steeper slopes may arise either by a large fraction of obscured young stars or by a significant fraction of unobscured old stars. Consequently, galaxies with older stellar populations exhibit steeper attenuation curves.…”
Section: Attenuation Lawmentioning
confidence: 59%
“…attenuation curve. Narayanan et al (2018b) investigated the main influence on the diversity of the slopes on a sample of "zoom-in" simulated galaxies and they highlight the importance of the star-to-dust geometry, i.e. high fraction of obscured young and low fraction of obscured old stars steepen the attenuation curve.…”
Section: The Eagle Simulations and The Skirt Post-processingmentioning
confidence: 99%
“…The effects of dust distribution geometry and stellar-age-dependent extinction make the attenuation curve significantly different from the original extinction curve (e.g. Inoue 2005;Narayanan et al 2018). We leave radiation transfer calculations and comparisons with observed attenuation curves for future work.…”
Section: Implication For Starburst Galaxiesmentioning
confidence: 99%